Roles of tax planning in market valuation of corporate social responsibility - Tye Wei Ling; Nor Shaipah Abdul Wahab (Cogent Business & Management, 2018)
This study aims to examine the roles of tax planning in market valuations of corporate social responsibility (CSR). Specifically, this study examines tax planning activities for their direct, mediating and moderating roles. As tax planning can undermine public's perceptions on company CSR due to the former's detrimental effects on society, understanding the nature of tax planning implications on shareholders' CSR valuations is crucial to draw a comprehensive conclusion on how tax planning can affect shareholders' perception on company CSR engagements. This study uses non-financial Malaysian-listed companies for 8 years from 2008 to 2015 as the sample. Tax planning is found to have significant negative direct and mediating roles in the equity valuations of CSR. On the contrary, tax planning is found to moderate the companies' market valuations of CSR positively, which suggests shareholders increasingly value company CSR and tax planning when shareholders consider both activities simultaneously in equity valuations. This study contributes to the body of knowledge by providing empirical evidence of a comprehensive view of tax planning effects on shareholders' CSR valuations. Practically, the findings are useful to industries, particularly in strategising the company CSR and tax planning activities. The findings can also benefit tax authorities in providing insights on potentials tax planning risks through CSR activities.
Keywords: 650